THE ROLE OF EUROPEAN FOOD SAFETY AUTHORITY IN THE ACTIVE SUBSTANCE APPROVAL AND RENEWAL PROCEDURES WITHIN THE EUROPEAN UNION PESTICIDE POLICY - Mladenović, Slađana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The EU decentralised agencies are involved in various sectorial EU policies and related composite procedures. One of the agencies, the European Food Safety Authority (EFSA), has a prominent role in the composite procedures within the EU pesticide policy – the active substance approval and renewal procedures. These procedures represent the initial steps in the complex administrative process of placing on the market and control of use of plant protection products. The procedures are arranged under the linear risk analysis model within which the scientific risk assessment is performed by Member States and EFSA, and political risk management is performed by the Commission and Member States in the comitology procedure. After a brief analysis of the key stages and outcomes of the procedures, the paper discusses two topics. The first relates to the properties of three key aspects of EFSA’s role in the procedures: 1) involvement in adopting guidance documents; 2) publishing appropriate documents and deciding on confidentiality requests; and 3) preparing and submitting the conclusion, its main scientific output related to active substance. The second topic includes five elements of confidence in EFSA regarding the course and outcome of the procedure: efficiency, independence, transparency, high scientific quality and effective risk communication. The paper discusses the properties of the elements, the main identified challenges associated with them, as well as ongoing and future responses to these challenges, especially those introduced by the Transparency Regulation, adopted in 2019 and applicable from 27 March 2021.